Complete dentures and oral health-related quality of life – do coping styles matter? - Heydecke G, Tedesco LA, Kowalski C, Inglehart MR (Blackwell Synergy, 2004)
Oral health-related quality of life (OHRQOL) in edentulous patients with complete dentures is often impaired.